(untitled) (Annals of Medical Research, 2024)
Aim: By studying children aged 0-6 with outpatient and health board admissions, we aimed to contribute valuable insights to the literature on early childhood support, focusing on admission complaints, diagnosis distribution, treatments, and patient follow-ups. Materials and Methods: Between 01.08.2022 and 01.02.2023 patients aged 0-6 from Diyarbakır Gazi Yaşargil Hospital’s Pediatric and Adolescent Mental Health and Developmental Pediatrics clinic, including those seeking health board evaluations, were studied. This prospective analysis examined patient demographics, complaints, diagnoses, health board interactions, treatments, and additional medical conditions. Patient follow-up numbers were scanned from the system for analysis before concluding the retrospective study. Results: Of the 600 patients included in the study, 337 patients came to the health board outpatient clinic, 160 to the child psychiatry outpatient clinic, and 103 to the developmental pediatrics outpatient clinic. 220 (36.7%) were female and 380 (63.3%) were male. The most common presenting complaints of the patients were speech delay, hyperactivity, report renewal, and irritability. In our study, the presenting diagnoses were global developmental delay, isolated speech delay, autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), articulation disorder, behavioral problems, stuttering, and specific learning disorder (SLD) with decreasing frequency. It was observed that 77.5% of the patients had no follow-up and the highest rates of follow-up were ADHD (67.4%) and ASD (56.9%). It was observed that 87.5% of the patients with a health board application had no follow-up. Conclusion: Determining the diagnosis, follow-up, and treatments of the patients may guide the areas in which child psychiatrists and developmental pediatricians should work more intensively in the future. Early diagnosis, screening initiatives, awareness campaigns, and training for parents, teachers, and health professionals, along with telehealth, multidisciplinary strategies, and school collaborations, enhance health board applications and patient follow-up.